SILICATE-PHOSPHATE INTERACTIONS IN SILICATE GLASSES AND MELTS: I. A MULTINUCLEAR (27AL,29SI,31P) MAS NMR AND AB INITIO CHEMICAL SHIELDING (31P) STUDY OF PHOSPHOROUS SPECIATION IN SILICATE GLASSES - Cody G.D.; Mysen B.; Sághi-Szabó G.; Tossell J.A. (My University, 2001)
An investigation of the structure of sodium aluminum silicate glasses [composition (x)Na2O, (1-x)Al2O3, 0.9SiO2 perturbed through the addition of 2 mol.% P2O5] was performed using a combination of 27Al, 29Si, and 31P solid state NMR spectroscopy and ab initio chemical shielding calculations (GIAO method). Speciation within these glasses was estimated using a physically consistent method for the deconvolution of inhomogeneously broadened 31P MAS-NMR spectra by employing a combination of spinning sideband analysis with the results of ab initio shielding calculations. A minimum of 13 different phosphorus-bearing species were estimated to contribute to the spectral complexity in these glasses over the compositional range investigated. The majority of these species are oxygen-bridged to the silicate lattice. These are described as (Al,Si)Qpn species, where n corresponds to the number of bridging oxygens (n = 1–4) and where there is variation in the Al/Si ratio of the tetrahedral nearest neighbors. In addition to the species bridging to the silicate lattice, nonlattice bridged Na-P type species, including ortho-, pyro-, and tripolyphosphates, are observed or deduced based on spectral behavior. A sharp crossover in the predominance of Na-P species relative to (Al,Si) Qpn dominant species occurs at low Al2O3 content. Within the group of nonbridging (Na-P) species, increased bulk aluminum content shifts the predominance from orthophosphate toward tripolyphosphate. Within the group of bridging [(Al,Si) Qpn] species, increasing bulk aluminum content shifts the predominance toward a greater number of oxygen bridges to the silicate lattice. To highlight the perturbative effect of 2 mol.% P2O5 addition on glass structure, 29Si MAS-NMR of P-bearing and P-absent glasses were compared. The speciation estimated from the combined 31P MAS-NMR and ab initio shielding calculations is consistent with 29Si MAS-NMR spectroscopic data. Analysis of 27Al MAS-NMR spectra for P-bearing and P-absent glasses reveals extensive Al-O-P interactions evident by systematic shifts in peak maxima to lower frequencies (greater shielding). Increases in the central transition peak half widths in the P-bearing samples reflect enhanced second-order quadrupolar interactions, also consistent with an abundance of (Al,Si) Qpn species. Analysis of the 27Al inner satellite transition sidebands reveals only a minor amount of VIAl. It is concluded that the addition of even a small amount of P2O5 (2 mol.%) results in a large perturbation of the structure of silicate glasses and should manifest significant effects on the physical properties of melts derived from them.